If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 49 + -7 = -6a + 12 Combine like terms: 49 + -7 = 42 42 = -6a + 12 Reorder the terms: 42 = 12 + -6a Solving 42 = 12 + -6a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '6a' to each side of the equation. 42 + 6a = 12 + -6a + 6a Combine like terms: -6a + 6a = 0 42 + 6a = 12 + 0 42 + 6a = 12 Add '-42' to each side of the equation. 42 + -42 + 6a = 12 + -42 Combine like terms: 42 + -42 = 0 0 + 6a = 12 + -42 6a = 12 + -42 Combine like terms: 12 + -42 = -30 6a = -30 Divide each side by '6'. a = -5 Simplifying a = -5
| -(6xy-11)+3(5xy+8)= | | X-4y+6z-5x-6x+y= | | -6xy-11+15xy+24= | | 2x+40=11x-50 | | 3b+4=4b-8 | | 10X-8=3X+6 | | 4y-8=2y-8 | | 8x+4x+2+5=9x+3+2x | | -20-10x=49-14x | | c=2000+1.65x+3600 | | 3n+4=1 | | 8(w+3)=48 | | -56=7y | | 4s-7=3s+3 | | -2x^2-22x+24=0 | | 7n+235n=59 | | 224(2)=x(2x-4)(2) | | 3y=27 | | 6x+12=12x-8 | | 62-2x=25x+17 | | 21y=5x | | 13-10x=5217x | | 57-6x=12x+15 | | 224=x(2x-4) | | 6x+13=-83-19x | | (19b-4)-9(2b+2)=-4 | | 3p-3=18 | | 9u-47=7(u-5) | | 12-j=6+j | | -4-6=11-9x | | 2x^2-4x-448=0 | | x+30+x-32=180 |